Aqueous phase reforming of glycerol to 1,3-propanediol using noble metal doped Ni/CeO2 - Siti Nor Amira, Rosli; Mohamad Razlan, Md Radzi; Syaza Izyanni, Ahmad; Mohd Hizami, Mohd Yusoff; Sumaiya, Zainal Abidin (Elsevier Ltd, 2025)
1,3-Propanediol, a vital compound with wide industrial applications, holds promise as a key product derived from aqueous phase reforming and in-situ glycerol hydrogenolysis. In this study, we are investigating the potential impact of noble metal (Ir, Pd, and Ru) doping on Ni/CeO2 catalysts, aiming to uncover the mechanisms responsible for enhanced reaction kinetics and catalytic performance. Our investigation thoroughly explores the physicochemical properties of the catalysts, utilizing many analytical techniques including FESEM-EDX, TEM, H2-TPR, NH3-TPD, BET, XRD, XPS, and ICP-OES. Within the controlled environment of our autoclave batch reactor, operating specifications of 20 % glycerol, 20 bar, and 230 °C are carefully maintained during the 3 h evaluation period. Among the synthesized catalysts, Pd-doped Ni/CeO2 stands out as the leading candidate, demonstrating superior physicochemical properties and catalytic effectiveness. Glycerol conversion rates soar up to 86.66 %, with 1,3-propanediol yields reaching 31.77 %. The kinetics reveal a compelling narrative of first-order reactions, supported by a modified Arrhenius equation featuring an activation energy of 12.203 kJ/mol and an R2 value of 0.947. This research marks a breakthrough in cost-effective, high-yielding glycerol transformation, signaling a notable shift in industrial catalysis. Noble metal-doped Ni catalysts are set to redefine traditional processes.